Implementasi Kegiatan Projek Penguatan Profil Pelajar Pancasila Tema Kearifan Lokal pada Tradisi Makan Bajamba - Nurfadhilah, Nurfadhilah; Martin Kustati; Gusmirawati; Rezki Amelia (STKIP PGRI Bandar Lampung, 2024)
This study aims to analyze the implementation of the project to strengthen the profile of Pancasila students (P5) on the theme of local wisdom in the tradition of eating bajamba. The type of research used in this research is field qualitative with a qualitative approach. The population in this study were all students who participated in the implementation of the Pancasila student project on the theme of local wisdom about eating bajamba with a sample in class IX. The data collection techniques used are observation, interview and documentation. The data analysis technique used is Miles and Huberman analysis with the stages of data reduction, data presentation and conclusion preparation. The results of this study indicate that the implementation of the Pancasila student profile strengthening project (P5) in junior high schools related to the theme of local wisdom in the tradition of eating bajamba has three stages: first, the preparation stage by designing the implementation of P5 through identifying the dimensions of P5 in accordance with the theme of local wisdom eating bajamba. Second, the P5 implementation stage with P5 training and management. Third, the evaluation stage through observation and assessment in the P5 implementation process.